[Tractors on airstrip for tractor pull] (1978)
One tractor has the sled attached to it from behind and another tractor is in the rear. Several men are on the airstrip looking at the sled. A crowd watches from the hillside and a sign hanging from a shed reads: 'Welcome tractor pull fans.' The old hanger can be seen in the distance.